(untitled) (International Conference on Computers in Education, 2016)
Disaster education focusing on how we should take immediate actions after disasters strike is essential to protect our lives. We proposed Immediate-Action Commanders (IACers) training and prototyped three IACers training systems using augmented reality (AR) and head-mounted displays (HMDs). The systems superimpose interactive virtual objects onto HMDs’ real-time vision or a trainee’s actual view.